2019
DOI: 10.1093/jnci/djz042
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Enriched Subtype and ERBB2 Expression in HER2-Positive Breast Cancer Treated with Dual HER2 Blockade

Abstract: Background Identification of HER2-positive breast cancers with high anti-HER2 sensitivity could help de-escalate chemotherapy. Here, we tested a clinically applicable RNA-based assay that combines ERBB2 and the HER2-enriched (HER2-E) intrinsic subtype in HER2-positive disease treated with dual HER2-blockade without chemotherapy. Methods A research-based PAM50 assay was applied in 422 HER2-positive tumors from five II–III clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 23 publications
6
104
1
Order By: Relevance
“…2). An analysis of baseline tumor samples from two clinical trials found that combined analysis of HER2E subtype and ERBB2 mRNA into a single assay identified tumors with high responsiveness to HER2-targeted therapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…2). An analysis of baseline tumor samples from two clinical trials found that combined analysis of HER2E subtype and ERBB2 mRNA into a single assay identified tumors with high responsiveness to HER2-targeted therapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical value of the HER2-E subtype in HER2+ breast cancer is starting to be elucidated. From a therapeutic perspective, the HER2-E subtype has shown, across 14 clinical trials and ∼2,000 patients, higher sensitivity to anti-HER2-based therapies than the non-HER2-E subtypes [7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, not all HER2-E tumors achieve a complete response following anti-HER2-based therapies.…”
mentioning
confidence: 99%
“…"Oncogene addiction" is used to describe tumors fully dependent on HER2 for proliferation and survival. These cancers are often exquisitely sensitive to HER2-directed therapy [16,17], even in the absence of Receptor pathways involved in the progression of breast cancer and mechanism of action of endocrine and targeted therapies. AI = aromatase inhibitor; AKT = protein kinase B; CDK = cyclin-dependent kinase; CoA = coactivator complex; CoR = corepressor complex; E2 = estradiol; EGFR = epidermal growth factor receptor; ER = estrogen receptor; EREs = estrogen receptor elements; ERK = extracellular signal-regulated kinase; HER2 = human epidermal growth factor receptor 2; IGF-1 = insulin-like growth factor 1 receptor; P = phosphorylation; PI3K = phosphatidylinositol 3-kinase; mTOR = mammalian target of rapamycin; Rb = Retinoblastoma protein (tumor suppressor protein); RE = response elements; RTKs = receptor tyrosine kinases; SERD = selective estrogen receptor degrader; SERM = selective estrogen receptor modulator; and TFs = transcription factors (e.g., activator protein 1 (AP-1), specificity protein 1 (SP-1), and E2 factor (E2F).…”
Section: Her2 Itselfmentioning
confidence: 99%